2023
DOI: 10.1186/s12957-023-02943-9
|View full text |Cite
|
Sign up to set email alerts
|

Reporting perioperative complications of radical cystectomy: the influence of using standard methodology based on ICARUS and EAU quality criteria

Abstract: Purpose We aimed to evaluate perioperative complications of radical cystectomy (RC) by using standardized methodology. Additionally, we identified independent risk factors associated with perioperative complications. Materials and methods We retrospectively analyzed 30-day and 90-day perioperative complications of 211 consecutive RC patients. The intraoperative and postoperative complications were defined according to Clavien-Dindo classification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…We estimate an expected absolute reduction of 17% in the complication rate or patients receiving preoperative IMN compared to patients receiving preoperative standard ONS. Postoperative complications following RC are known to occur in approximately 64–70% of patients without nutritional supplementation [ 4 , 18 ]. A small randomised pilot study showed a 30-day complication rate of around 73% in patients receiving standard ONS [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…We estimate an expected absolute reduction of 17% in the complication rate or patients receiving preoperative IMN compared to patients receiving preoperative standard ONS. Postoperative complications following RC are known to occur in approximately 64–70% of patients without nutritional supplementation [ 4 , 18 ]. A small randomised pilot study showed a 30-day complication rate of around 73% in patients receiving standard ONS [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the following reported inflammatory-nutrition biomarkers were calculated based on the preoperative blood tests: Neutrophil-to-lymphocyte ratio (NLR) [ [9] , [10] , [11] ]. Platelet-to-lymphocyte ratio (PLR) [ 9 , 10 , 12 , 13 ]. Systemic inflammation response index (SIRI) [ 13 ], and Prognostic nutritional index (PNI) [ [13] , [14] , [15] ].…”
Section: Methodsmentioning
confidence: 99%
“…2 Side effects are related to treatment selection ranging from adverse reactions to chemotherapy and radiotherapy, to intraand post-operative complications associated with surgery. 3,4 Despite the high incidence, relatively little is known about patient experience of bladder cancer, as highlighted in a recent systematic review. 5 However, this information is important when helping patients to select management options and should also guide improvements to patient care pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Management strategies typically include endoscopic resection, radiotherapy, chemotherapy, immunotherapy and radical surgical approaches such as cystectomy 2 . Side effects are related to treatment selection ranging from adverse reactions to chemotherapy and radiotherapy, to intra‐ and post‐operative complications associated with surgery 3,4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation